Evaluation of the effectiveness of spraying operations carried out by a drone/unmanned aerial vehicle (UAV) in comparison to the conventional approach forthe management of safflower aphids (Uroleucon compositae Theob) and safflowercapsule borer (Helicoverpa armigera Hubner): Evaluation of the effectiveness of spraying operations carried out by a drone/unmanned aerial vehicle (UAV) in comparison to the conventional app - T RAJESHWAR REDDY; C SUDHAKAR; C SUDHA RANI; C MANIKYA MINNIE (Journal of Oilseeds Research, 2023)
The safflower variety ISF-764 was sown in the second fortnight of November, 2020. The Experiment comprised of three treatments Viz., T1: Spraying of Emamectin Benzoate 5% SG (200g /ha), Imidacloprid 17.8 SL (200ml /ha) with UAV; T2: Spraying of Emamectin Benzoate 5% SG (200g /ha) and Imidacloprid 17.8 SL (200ml/ha) with a power sprayer and T3: Untreated control. Both sprayers performed well in the management of Helicoverpa and Aphids. No Helicoverpa larval and Aphids populations were registered in T1: Spraying of Emamectin Benzoate 5% SG (200g /ha), Imidacloprid 17.8 SL (200ml /ha) with UAVs at 3DAS, 10 DAS, respectively. The highest seed yield benefit cost ratio were ecorded in the plot sprayed with UAVs (1691 kg /ha& 4.36).